Utilization of Aloe Vera as a Biocoagulant in the Treatment of Domestic Wastewater (Grey Water) Based on TSS and Total Coliform Parameters: Pemanfaatan Aloe vera Sebagai Biokoagulan Pada Pengolahan Air Limbah Domestik (Grey Water) Pada Parameter TSS dan Total Coliform - Arristo Pancis Simanjorang; Wilma Nurrul Adzillah; Firda Ainun Nisah (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Domestic wastewater, which is categorized into black water and grey water, is one of the main sources of water pollution due to its high concentrations of Total Suspended Solids (TSS) and Total Coliform, both of which negatively impact human health and the environment. This study aims to evaluate the effectiveness of Aloe vera as a biocoagulant in reducing TSS and Total Coliform concentrations in domestic wastewater from Housing Complex X, Sirnabaya Village, Karawang Regency, as well as to compare its performance in gel and liquid forms. The research method applied was a laboratory scale experiment using the jar test. Wastewater samples were collected through composite sampling at three different times in one day (08.00, 14.00, 20.00 WIB). The Aloe vera biocoagulant was processed in two forms: gel and liquid. Dosage variations tested were 0, 10, 15, 20, and 25 mL/L. The results showed that the Aloe vera biocoagulant was effective in reducing both TSS and Total Coliform. In the gel form, with the dose of 25 mL/L reached the result 86% for TSS and 76% for Total Coliform, meanwhile for the liquid form reached the result 76% and 73% with 10 mL/L dose. The superior performance of the gel form compared to the liquid is attributed to its more intact active compounds, such as acemannan for TSS and anthraquinones for Total Coliform.